Faktor-faktor yang Mempengaruhi Kesiapsiagaan Bencana Gempa Bumi Pada Lansia di Posyandu Puntodewo Tanjungsari Surabaya - Wijaya, Siswato Agung; Wulandari, Yuanita; Lestari, Rizqi Indah (Jurnal Keperawatan Muhammadiyah, 2019)
Introduction: Elderly is a vulnerable group that has the potential to increase morbidity in the earthquake disaster in Surabaya because the elderly have a decreased physical ability in disaster preparedness. The purpose of this study was to determine the factors that affect earthquake preparedness in the elderly in the Puntodewo Posyandu Surabaya.Method: This study used a quantitative descriptive research design with a cross-sectional approach, with the elderly population in the Posodandu Puntodewo included in the inclusion and exclusion criteria. The study selected respondents with purposive sampling with a sample size of 110 respondents. Data collection tools used a questionnaire. Data were analyzed using the chi-square test and the Spearman test.Results: Chi-Square test results showed no relationship between age factors and preparedness Ï = 0.507> É‘: 0.05, there was a relationship between educational level factors and preparedness Ï = 0.008 <É‘: 0.05. The Spearman test results showed that there was no correlation between knowledge factors with preparedness, Ï = 0.819> É‘: 0.05 and there was a relationship between experience and preparedness Ï = 0.000> É‘: 0.05.Conclusion: Earthquake disaster preparedness in the elderly is influenced by several factors namely the level of education and experience factors.Keywords: Influencing factors, preparedness, elderly